TOKOH UTAMA NOVEL PRIA TERAKHIR KARYA GUSNALDI KAJIAN PSIKOANALISIS - Erlina Erlina (Ensiklopedia of Journal, 2022)
This research is motivated by the main character's Pria Terakhir novel by Gusnaldi to study psychoanalysis. Personality, temperament and character refers to the nature and attitude of the figures as interpreted by the reader. Characterizations are description of a man featured in a story. The term psychoanalysis is a view of human beings, where the unconscious deadly central role in the entire life of the human psyche. This study aims to (1) describe the personality of the main character's Pria Terakhir by Gusnaldi novel aspect of the id; (2) describe the personality of the main character's Pria Terakhir by Gusnaldi novel aspect of ego; (3) describe the personality of the main character's Pria Terkahir by Gusnaldi novel aspect of the superego. The research is a qualitative study using descriptive methods. The object of this research is the novel's Pria Terakhir by Gusnaldi. This study focused on psychoanalysis character in the novel's Last Men Gusnaldi. Data collection techniques in this study are (1) establishes the main character by using the data format of the main character, and (2) identify the psychiatric main character is based on psychoanalysis Sigmund Freud. While the steps in analyzing the data, namely: (1) classify data based on the id, ego and superego; (2) analysis of data based on the id, ego, and superego; (3) The interpretation of the data; (4) concluded; (5) a research report. The results of this study indicate that the characters in the novel Bobi's Pria Terakhir character by Gusnaldi novel friendly, patient, never denied, compassionate, passion and effort.Keywords: the main character, novel, psychoanalysis.